Proceedings of the Workshop on Experiences with Modern Rice Cultivation in Bangladesh, 8-10 June 1993. - Workshop on Experiences with Modern Rice Cultivation in Bangladesh 1993 : Bangladesh Rice Research Institute); Bangladesh Rice Research Institute; Bangladesh. Dept. of Agriculture Extension (Gazipur : Bangladesh Rice Research Institute, 1994)
Papers presented at the 16th national workshop.
Includes passages in Bengali.
"Theme: Rice production in a changing environment."
"Jointly sponsored by Bangladesh Rice Research Institute and Department of Agriculture Extension."
Includes bibliographical references (p. 133).
Keywords: Rice -- Bangladesh -- Congresses; Rice -- Varieties -- Bangladesh -- Congresses